Alternative to Hormone Therapy for Reproductive Infringements in Girls-Teenagers (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The problem of girls' reproductive health and their reproductive potential as expectant mothers attracts close attention of scientific researchers, since along with medical significance, it is increasingly gaining social significance. Negative trends in the medical and demographic situation (increasing morbidity of the population, environmental stresses) strongly dictate that special attention should be paid to the reproductive health of the younger generation [1,2]. The frequency of disorders in the development of the reproductive system and deviations in the psychosomatic health of adolescents has increased.